Annual report 2017: CGIAR Research Program on Climate Change, Agriculture and Food Security - CGIAR Research Program on Climate Change, Agriculture and Food Security (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2018)
CCAFS made considerable progress on the CCAFS SLO target of 11 million more households with improved practices, with some 6.5 million farmers being better serviced by climate-informed advisories (Philippines, Rwanda, Colombia, Senegal – IRRI, IRI, CIAT), receiving climate-smart seed (Ethiopia – Bioversity), or being part of a program that will deliver solar-based irrigation (India – IWMI/WLE), where CCAFS research has informed a USD 21.5 billion investment. Initial monitoring and evaluation (M&E) results from Rwanda show that over 85% of participating farmers (both women and men) change their farm or livelihood management in response to advisories, and share the information with more than 10 peers. These efforts are receiving due recognition, with the Rwanda work receiving a Climate Smart Agriculture (CSA) Project of the Year Award. CCAFS’ work also pays close attention to gender and social inclusion. For example, in Ethiopia, slightly over half of the 1.3 million farmers reached are estimated to be women. A gender- sensitive framework for prioritization of CSA interventions was developed and used to identify location- specific gender-responsive CSA interventions that are being implemented through women farmers’ leadership in Climate-Smart Villages (CSVs). Investments that promote climate smart practices were informed by CCAFS science in CSVs, including USD 170 million for Happy Seeder technology (targeting 2 million farmers) in India and USD 66 million in Cauca, Colombia, to scale up CSA. Further CCAFS science- informed investments by the World Bank, African Development Bank and the cocoa industry are also in the pipeline.